The Effectiveness of the Combination of Aromatherapy and Back Massage on Normal Labor Pain Intensity in Stage I of Active Phase in Puskesmas Pontianak City Indonesia - Sudarto; Halina Rahayu (Britain International for Academic Research (BIAR) Publisher, 2021)
Parturition pain is a problem that is felt by a mother during labor that causes excessive fear and anxiety to the mother and her family so that intervention is needed in dealing with pain. The purpose of this study to analyze the effectiveness of combination of aromatherapy and back-massage on parturition pain during the first stage of active phase of normal labor. This study used a quasi-experimental design with two groups with a sample of 60 mothers. This research was conducted at a community health center that provides maternity services in Pontianak City. Pre-test and post-test nonequivalent control group design was conducted where the researcher did not do randomization. Data were analyzed using the Wilcoxon test. The test results showed that the intervention group had a value of ρ 0,0001 <0.05 and the control group produced a value of ρ 0.001 <0.05. This means there are differences in the level of pain before and after treatment. Likewise, the Mann-Whitney U-Test statistical test results showed a value of ρ 0.001 <0.05, which means that there are differences in pain intensity between the group of mothers who were given a combination of aromatherapy and back massage and the other group of mothers who got deep breathing relaxation during the process of labor. The combination of aromatherapy and back massage is effective in reducing pain in normal labor in the first phase of the active phase. This therapy is expected to be used as an alternative intervention for a mother in active phase of labor, especially to reduce the intensity of pain in the first phase of the active phase of normal labor.